Inverse Kinematics and PID Controller Implementation of Hexapod Robot for Wall Follower Navigation - Riky Tri Yunardi; Arief Muchadin; Kurnia Latifa Priyanti; Deny Arifianto (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2019)
Wall following is one of the methods used in navigating the movement of robot applications. Because the robot moves along the wall, the ultrasonic sensor is used as a barrier detector capable of measuring the distance between the robot and the wall. The six-legged robot is a hexapod robot has six pieces of legs and each leg has three joints that are used to move. The leg movement is based on the inverse kinematics to obtain the angle value of each joint. Nevertheless, a six-legged robot requires stability in order to move smoothly while following the wall. In this work, a robot was developed using a proportional derivative controller to implemented on wall follower navigation. The PID controller is determined using analytic tuning to produce the controller parameters that are used to make the robot move straighten and keep the position against the wall. Overall, the application of inverse kinematics and PID control on the wall following robot navigation can improve the stability of the robot with a set point value of 8-16 cm on the wall length of 1.5 within 9296 % of average success rate.